Dynamics of the defect-mediated desorption of alkali halide surfaces - Szymonski, M.; Droba, A.; Struski, P.; Krok, F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Dynamic processes leading to desorption of Rb and I atoms from the RbI (100) surface co-irradiated with 1 keV electrons and visible light (with a wavelength corresponding to the F-center absorption band) have beenstudied by means of mass-selected time-of-flight (TOF) spectroscopy. Depending on the sample temperature, substantial enhancement of the desorption yield, as well as pronounced changes in the TOF spectra of the emitted atoms have been found. The TOF spectra of halogen atoms consist of two components: thermal (which can be fitted with Maxwellian distribution) and non-thermal one. The non-thermal peak is temperature-independent. There is no non-thermal component for alkali atoms. The comparison of TOF spectra for I atoms emitted from electron bombarded sample with and without simultaneous light irradiation indicates that the yield increase is caused by thermally desorbed atoms, while the non-thermal peak remains unchanged. Presented results confirm well the predictions of the theoretical model of desorption proposed earlier, known as the defect-mediated (F and H center) desorption of alkali halides.